Predicting consumer intentions to shop herbal products online: an empirical investigation - Mohd Zahran, Muhammad Zaid; Rezai, Golnaz; Mohamed, Zainalabiddin (2012)
The burgeoning market for herbal products in Malaysia along with government support and access to cheaper production methods has led to the production of more and more local herbal products by Small and Medium Enterprises (SMEs). However in contrast to the imported products brought in by large importers, the local SMEs have limited capital and resources with which to market and distribute their products, often competing for limited shelf space in stores. The similarly increasing internet use in Malaysia provides a potential solution to this problem. Hence this study sets out to identify the factors which can be used to predict a consumers’ intention to buy an herbal product online using a binary logistic regression model based on the Theory of Planned Behaviour framework. A structured selfadministered questionnaire was distributed via email to internet users residing in Peninsular Malaysia. A total of 1063 users completed the questionnaire. The collected data was then analysed for demographic characteristics and TPB-based factors identified beforehand. The factors which have been found significant in predicting the intention of an average Malaysian to shop online for an herbal product are: Age, Gender, Marital Status, Income, Internet Speed and Experience, Herbal Products Characteristics, Perceived Benefits, Subjective Norm, Payment Method and English Proficiency. The results of the logistic regression model hint that by taking steps such as widening payment options, providing English and Malay version of websites, and gaining good safety and health certifications, among other factors, SMEs could increase the likelihood of consumers to purchase herbal products online.